Theory of Classical Gaussian Observer (Global Journal of Science Frontier Research, 2017)
This paper treats the concept of the Gaussian probability distribu- tion both for the target and observer. The resulting observations become Gaussian distributions as well. The time coordinate gets an equal set- ting as any physical quantity. This treatment is purely classical with no essential reference to quantum mechanics nor to theory of relativity.1 2
Keywords: measurement; observation of physical quantity; gaussian observer; classical observer